Luminescence of europium(III) and manganese(II) in barium and zinc orthosilicate - Pires, Ana Maria [UNESP]; Davolos, Marian Rosaly [UNESP] (Amer Chemical Soc, 2001)
The aim of this work is to report on the luminescence properties of BaZnSiO4 activated by Eu3+ and Mn2+ ions. Doped and undoped powder samples were prepared by solid-state reaction starting from oxides and carbonates or Ba2SiO4:Eu3+ and Zn2SiO4:Mn2+ precursors. X-ray diffraction powder data, IR vibrational, and UV-vis luminescence spectroscopies were carried out. Results showed that doped and undoped samples from both types of precursors have the same structure and crystallize with a superstructure of hexagonal kalsilite. Vibrational spectroscopy has confirmed the formation of a silicate group, which outlines differences between products and silicate precursors. The observed luminescence assigned to Eu3+ and Mn2+ transitions covered most parts of the visible spectrum, an important requirement for phosphors in fluorescent low-pressure mercury vapor lamps.